Unions and collective bargaining - Brändle, Tobias (Global Labor Organization (GLO), 2024)
Unions and collective bargaining play a central role in shaping wages and influencing firms' employment decisions and firm survival, especially in industrialised countries, and where they are traditionally strong. Their impact depends on the institutional role unions (can) play in different countries, on the economic conditions, and it varies strongly between industries. Overall, the literature has analysed union wage effects quite extensively, and to a lesser degree also their effects on employment. Unions typically increase wages and other working conditions for their members and often all employees working in firms where collective bargaining applies. There is strong evidence for a union-non-union wage premium, even for individuals working similar jobs. At the same time, wages are higher in firms under collective bargaining, even in similar firms in the same industry. The size of these premiums can vary widely, however, between countries, time periods, and context. The union wage premium is typically stronger at the lower end of the wage distribution, such that strong unions are associated with lower wage inequality. This result is more or less undisputed in the literature. The union effect on employment is theoretically more ambiguous, but empirically labelled as 'the one constant' among the effects of unions: employment growth is two to four percent lower in firms with union bargaining. There may, however, also be positive effects of union bargaining on the quality of employment or employment duration from an individual perspective. A union effect on firm survival is the least well analysed among the three effects presented here. If unions redistribute rents to employees and if 'the one constant' holds, then firm survival might be negatively affected by union bargaining. The empirical evidence is, however, inconclusive.
10419/300248
Keywords: Graue Literatur; collective bargaining; trade unions; wages; employment; firm survival